Tax Management in The Indonesian Banking Sector: The Moderating Role of Independent Commissioners on The Relationship Between Profitability and Firm Size Toward Effective Tax Rate - RR. Maria Yulia Dwi Rengganis; Ni Luh Nyoman Sherina Devi; Ni Kadek Dwi Antari; Desak Made Sri Juniasri Dewi (AIBPM Publisher, 2025)
Tax management is a key strategy for business entities to meet their tax responsibilities efficiently and legally. The purpose of this study is to examine how profitability and firm size impacts on tax management, as measured by the Effective Tax Rate (ETR), and the moderating role of independent commissioners in Indonesian banking companies from 2021 to 2023. The results show that profitability has a significant negative effect on ETR, while firm size has no effect. The interaction test shows that independent commissioners significantly moderate the relationship between profitability and ETR by weakening the negative effect. However, independent commissioners' moderating influence on the association between company size and ETR is statistically insignificant. These findings highlight the importance of good corporate governance, particularly the monitoring function of independent commissioners, in encouraging the responsible of tax behavior. The contributions of this study add to the literature on tax management and also corporate governance, and provides knowledge for regulators to strengthen tax compliance mechanisms in the banking sector.